2018
DOI: 10.1007/978-3-030-05195-2_39
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study on LTE Handover and the Impact of Cell Size

Abstract: In this paper we address the impact of cell size on the handover procedure in a Long Term Evolution (LTE) network. In particular, we highlight the potential problems that may occur when small cell densification is applied. In addition, the impact of the User Equipment (UE) speed is also analyzed. System level simulations are provided using a detailed LTE network simulator accounting for multiple points-of-failure and channel modeling compliant with LTE standards. We conclude that a certain cell size can be fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…The second cause is linked to especially the low ISDs. In our previous work [19], we found that the failures due to timer T310 expiry before HOcmd reception are very frequent when ISD is small and low when the ISD increases. We argued that for small cell sizes, the UEs that are able to transmit the measurement report subsequently move out of the serving cell coverage, and thus the HO command, sent by the serving cell, cannot reach the UE.…”
Section: Ue Received Power Consumptionmentioning
confidence: 83%
See 4 more Smart Citations
“…The second cause is linked to especially the low ISDs. In our previous work [19], we found that the failures due to timer T310 expiry before HOcmd reception are very frequent when ISD is small and low when the ISD increases. We argued that for small cell sizes, the UEs that are able to transmit the measurement report subsequently move out of the serving cell coverage, and thus the HO command, sent by the serving cell, cannot reach the UE.…”
Section: Ue Received Power Consumptionmentioning
confidence: 83%
“…The lowest power consumption is attained for ISD 500m, which constitutes an "optimum" ISD under the simulated assumptions. An ISD of 500m turns to be optimal since we are able to avoid the UL impairment problems arising for small ISDs (due to high interference from neighboring UEs) and large ISDs (due to low UE transmitted power at the cell edge), see also [19]. The other trend of the graph shows that increasing UE speed, increases power consumption, especially at low ISDs, due to the high signaling rate observed in Fig.…”
Section: Ue Transmitted Power Consumptionmentioning
confidence: 84%
See 3 more Smart Citations